First record of Longidorella xenura and Oriverutus parvus (Nematoda: Nodiidae) in Cuc Phuong national park, Vietnam - Anh Duong, Nguyen Thi; Thanh Tam, Vu Thi; Peña-Santiago, Reyes (Academia Journal of Biology, 2013)
Longidorella xenura and Oriverutus parvus from Cuc Phuong National Park are described and illustrated for the first time in Vietnam. Longidorella xenura species is characterized by its small body 0.72 mm long; lip region continuous; odontostyle typical of the genus, slightly arched; odontophore linear, rod-like; female genital system didelphic-amphidelphic; tail conical elongated with finely rounded tip. Oriverutus parvus species is characterized by its body 0.64-0.68 mm long; lip region slightly angular, offset by depression or weak constriction; lips moderately amalgamated with protruding papillae but not typically lobe-like; odontostyle moderately robust; odontophore rod-like; female genital system didelphic-amphidelphic; tail conical with pointed tip.